(untitled) (Orfeu, 2023)
Although it is not configured as an obligation from a legal point of view, in-clusive teaching in the training of teach-ers, it is a demand that originates from the field of work of the music graduate, since, at some point in his teaching career, He will work with people with disabilities, if he does not teach but is inclusive or at the same time in special education. It is un-derstood, therefore, the need for special and inclusive education to be contem-plated in the training period of the music graduate, with the aim of preparing the student for these teaching and learning situations. The objective of this experi-ence report is to share the pedagogical process of an optional discipline of spe-cial and inclusive education in the context of a music degree course at a Public High-er Education Institution. By means of re-cords made from ethnographic research principles and instruments, we expose the situations of teaching or learning that are organized from Freirean methodological principles, as well as the reflections and results. In this way, the need for this con-tent to be part of the training of the music teacher at graduation is highlighted, and it presents a possibility of structuring the pedagogical proposal of the discipline.